Macquarie Surgical Innovation Identification Tool (MSIIT): a study protocol for a usability and pilot test. Issue 11 (18th November 2016) - Blakely, Brette; Selwood, Amanda; Rogers, Wendy A; Clay-Williams, Robyn
Abstract : Introduction: Medicine relies on innovation to continually improve. However, innovation is potentially risky, and not all innovations are successful. Therefore, it is important to identify innovations prospectively and provide support, to make innovation as safe and effective as possible. The Macquarie Surgical Innovation Identification Tool (MSIIT) is a simple checklist designed as a practical tool for hospitals to identify planned surgical innovations. This project aims to test the usability and pilot the use of the MSIIT in a surgical setting. Methods and analysis: The project will run in two phases at two Australian hospitals, one public and one private. Phase I will involve interviews, focus groups and a survey of hospital administrators and surgical teams to assess the usability and system requirements for the use of the MSIIT. Current practice regarding surgical innovation within participating hospitals will be mapped, and the best implementation strategy for MSIIT completion will be established. Phase II will involve trialling the MSIIT for each surgery within the trial period by various surgical personnel. Follow-up interviews, focus groups and a survey will be conducted with trial participants to collect feedback on their experience of using the MSIIT during the trial period. Comparative data on rates of surgical innovation during the trial period will also be gathered from existing hospital systems and compared to the rates identified by the MSIIT. Ethics and dissemination: Ethical approval has been obtained. The results of this study will be presented to interested health services and other stakeholders, presented at conferences and published in a peer-reviewed MEDLINE-indexed journal.